Pelatihan Model Pembelajaran Mata Pelajaran Bahasa Indonesia - Agus Hamdani; Zoni Sulaiman; Ari Kartini; lin Siti Nurwahidah; Nuri Yulhani Alfiah (Jurnal Pekemas, 2019)
Indonesian language learning in schools must be carried out with various methods so that students are not bored in learning. The cooperative learning model is one of the learning models that can activate students so that it is very suitable for use in learning Indonesian. The results of the author's observations show that teachers in the field often only use conventional learning models because they rarely master various learning models that activate students. This community service activity aims to provide training in the application of various cooperative learning models for teachers in Wanaraja District, Garut Regency. Through this service activity, it is hoped that teachers will be able and skilled in using various cooperative learning models in teaching and learning activities in the classroom. The benefits obtained from this activity are that with the skills possessed by the teacher, students can learn Indonesian subjects in a fun method so that all the basic competencies proclaimed in the learning curriculum can be achieved.